Herbal footbaths for insomnia treatment in cancer patients - Minh, Tran Le; Quang, Mai Ba; An, Tran Thien; Thanh, Duong Huu; Anh, Nguyen Phan Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Sleep disorders and insomnia are frequent concerns among cancer survivors, presenting a notable challenge. Herbal footbaths are a complementary and alternative medicine that provides good results in managing insomnia, with few adverse effects and low costs. This study aims to assess the effectiveness and safety of herbal footbaths therapy for insomnia treatment in cancer patients. Methods: A cross - sectional descriptive study was carried out on 63 inpatients with cancer undergoing treatment at the Oncology Center in Hue Central Hospital. The primary outcome was the Insomnia Severity Index (ISI). The secondary outcome was adverse therapy reactions. Results: The ISI scale reduced significantly to 4.92 ± 2.55 (p < 0.01). No adverse reactions were found during the study. Conclusion: Herbal footbaths are an effective and safe treatment for insomnia in cancer survivors.